Relay exchanges in elite short track speed skating. Issue 5 (28th May 2017) - Hext, Andrew; Heller, Ben; Kelley, John; Goodwill, Simon
Abstract: In short track speed skating, the relay exchange provides an additional strategic component to races by allowing a team to change the skater involved in the pack race. Typically executed every 1½ laps, it is the belief of skaters and coaches that during this period of the race, time can be gained or lost due to the execution of the relay exchange. As such, the aim of this study was to examine the influence of the relay exchange on a team's progression through a 5000 m relay race. Using data collected from three World Cup relay events during the 2012–2013 season, the time taken to complete the straight for the scenarios with and without the relay exchange were compared at different skating speeds for the corner exit prior to the straight. Overall, the influence of the relay exchange was found to be dependent on this corner exit speed. At slower corner exit speeds (12.01–13.5 m/s), relay exchange straight times were significantly faster than the free skating scenario ( P < 0.01). While at faster corner exit speeds (14.01–15 m/s), straight times were significantly slower ( P < 0.001). The findings of this study suggest that the current norm of executing relay exchanges every 1½ laps may not be optimal. Instead, varying the frequency of relay exchange execution throughout the race could allow: (1) time to be gained relative to other teams; and (2) facilitate other race strategies by providing an improved opportunity to overtake.